PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KUALITAS PEMBELAJARAN SISWA BERKEBUTUHAN KHUSUS DI SDN TANAH SEREAL 03 - puji prayogo (LP2M JAMIAT KHEIR, 2026)
ABSTRACT ​This study aims to evaluate the role of Islamic Religious Education (PAI) teachers in improving the learning quality of inclusive students at SDN Tanah Sereal 03. PAI teachers have a strategic role in making learning flexible and inclusive in accordance with the characteristics and needs of students with special needs. This study was conducted using a qualitative approach and case study. Data were collected through interviews and thorough observations with PAI teachers, school principals, and students, as well as relevant documentation. The process of data reduction, presentation, and conclusion drawing was used to analyze the data. ​The results of the study indicate that PAI teachers teach, assist, encourage, guide, and evaluate the learning process. To improve inclusive education, various learning methods are used, materials are adjusted to students' abilities, engaging learning media are provided, continuous motivation is given, and a friendly and comfortable learning environment is created for students with special needs. Therefore, to maximize inclusive education, school support, ongoing teacher training, and better learning facilities are required. ​Keywords: The Role of Islamic Education Teachers, Learning Quality, Inclusive Students, Inclusive Education